Social Return on Investment of PT Badak NGL SALIN SWARA Program - Dwi Thia Putri; Irfan Hidayat; Yuli Gunawan (Economics Development Analysis Journal, 2022)
PT Badak NGL through its CSR (Corporate Social Responsibility) programs contributes to Sustainable Development (SDGs) realization. One of its CSR programs is Salin Swara which is related to a community waste program aiming at creating society’s collective awareness of common waste and household waste management to preserve the environment. This quasi-qualitative study attempted to assess the social impact received by salin swara stakeholders and the amount of social impact resulting from this program compared to the investment made by PT Badak NGL. In data analysis, this study used triangulation techniques to map the advantages of this program (qualitative) and the Social Return on Investment-SROI method (quantitative). To collect the data, in-depth interviews, Focus Group Discussions, and secondary data reviews were done. Practically this study provides an overview for companies to evaluate their CSR programs using the SROI method, while the results can be a basis for optimizing the next CSR program. Based on the SROI method, Salin Swara program gained a score of 2.33, meaning that the program benefitted 2.33 times the investment issued. In addition, the value of it’s benefit was Rp.31,302,849 with a total investment of Rp.13,437,500.00. The outcome value was dominated by the outcome of the workers Social Security Agency or BPJS Ketenagakerjaan death insurance claims (67%). It shows good program performance because the payback period has been obtained in the same year when the program was carried out